OPTIMASI PENUGASAN KARYAWAN PADA CV. MULIA ABADI DENGAN METODE HUNGARIAN - Tiar Mirnasari; Wulandari Wulandari; M. Chandra Leka (FEB Institut Bakti Nusantara, 2021)
Abstract This study aims to determine the optimal allocation of labor and minimum labor assignment costs. Research objects in this research are employees of PT. Mulia Abadi. This type of research in this research is using qualitative descriptive with data methods using primary and secondary data. The data technique uses observation, interviews, documentation and literature. The sample technique used in the study was population technique. From the results of the research workforce assignment, the calculation results that have been optimal, namely: machine regulation by labor No. 5, the machine record on the labor No. 4, the printing press at work force No. 8, machine cut labor line No. 2 compiler machines with labor No. 6, the binding machine on the labor No. 3, machine trim on labor No. 4 and packing with labor No. 7. Changes in the workforce assignment made can reduce the cost of the assignment that must be borne by the company. The cost of a new assignment for existing workers is Rp. 5,362.92, which means a reduction in costs of Rp. 2,006.25 less and the cost of the assignment so far is Rp. 7,369.17 (Attachment 2) and lower Rp. 1,487.08 and the cost that has been planned so far is Rp. 6,850.00.